Fake news anatomy study. Qualitative methods of analyzing disinformation posted on the Internet - Jarzyńska, Katarzyna (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume II, 2023)
Fake news are information, messages or entries that provide false or distorted data. Their main purpose is to mislead the audience, cause feelings of shock and disbelief, and cause controversy. The aim of the study is to identify methods of qualitative analysis of (dis)information that can be used to study the anatomy of fake news. A set of selected information collected from various sources was analyzed, including from Twitter. The results of the study allow for the identification of the characteristic features of false information and are able to aid faster detection of fake news.